The Passion Scale—Portuguese Version: Reliability, Validity, and Invariance of Gender and Sport. Issue 4 (August 2019) - Cid, Luis; Vitorino, Anabela; Bento, Teresa; Teixeira, Diogo S.; Rodrigues, Filipe; Monteiro, Diogo
The aim of this study was to analyze the psychometric properties of the original version of the Passion Scale (14 items, two factors). We tested it within a sample of mixed gender Portuguese athletes from different sports, including adapted sports. In addition to demonstrating reliability, validity, and confirmatory factor analyses of the Passion Scale, we sought to analyze the invariance of this measure between males and females and across six types of sports (soccer, futsal, swimming, surf, bodyboard, and adapted sports). We recruited 1, 316 athletes to test this scale from both genders (1, 109 males; 207 females), aged 14–59 years ( M = 21.83; SD = 8.67). Our main results revealed weaknesses in the factor model for the original instrument (14 items and two factors) leading us to reject the model. However, after adapting the model (to eight items and two factors), the psychometric properties of the Passion Scale improved substantially and then exhibited (a) good fit to the data and (b) invariance between gender and across sports. Our new proposed version of the Passion Scale can be used with confidence to analyze the passion athletes feel when practicing their sport.